1983
DOI: 10.1073/pnas.80.10.3045
|View full text |Cite
|
Sign up to set email alerts
|

Functional clonal deletion of cytotoxic T-lymphocyte precursors in chimeric thymus produced in vitro from embryonic Anlagen.

Abstract: Chimeric thymus, formed by fusing the prelymphoid third pharyngeal pouches of fetal mice with fetal liver, have been allowed to develop entirely in vitro. Syngeneic and allogeneic chimeras were prepared and both types of thymus were shown to contain substantial numbers of functional cytotoxic T lymphocyte precursors reactive against "third party" alloantigens. However, alloreactivity specific for H-2 antigens present on either the third pharyngeal pouch or the fetal liver was minimal. In three different alloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In other models, using either TCR transgenic mice or deletion by superantigens of T cells bearing certain TCR Vp chains, partial deletion of reactive T cells by TE has been described in some models (4,(19)(20)(21)(22), whereas others saw no effects (17,26). Interestingly, Schonrich et al (17), using the same Kb-specific Des-TCR transgenic mice that we used in the present study, reported that expression of Kb on medullary TE did not induce deletion of Des-TCR+CD8+ T cells in the thymus.…”
Section: Resultsmentioning
confidence: 99%
“…In other models, using either TCR transgenic mice or deletion by superantigens of T cells bearing certain TCR Vp chains, partial deletion of reactive T cells by TE has been described in some models (4,(19)(20)(21)(22), whereas others saw no effects (17,26). Interestingly, Schonrich et al (17), using the same Kb-specific Des-TCR transgenic mice that we used in the present study, reported that expression of Kb on medullary TE did not induce deletion of Des-TCR+CD8+ T cells in the thymus.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies as well as in the present one, the limiting-dilution curves obtained were linear and applied to zero-order kinetics, which indicates that only one cell type was limiting for the response. This constituted one argument in favor of a mechanism of functional clonal deletion rather than of active suppression (3,18). On the other hand, it cannot be excluded that the frequency of suppressor cells in these cultures is so high that they cannot be isolated from cytotoxic precursor cells by the means of limiting dilution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the questions of the site of tolerance induction and the mechanisms involved are uncertain. In a recent report, embryonic thymic epithelial rudiments, removed prior to their population by migrant stem cells, were cultured with fetal liver fragments as a source of stem cells (Good et al, 1983). The thymus cultures, when harvested, were examined in limiting dilution assays for precursors of cytotoxic cells to MHC antigens of the fetal liver donor, thymus epithelium, and third party, respectively.…”
Section: Early Differentiation Of the Thymic Stroma And Its Influencementioning
confidence: 99%